Real-life data on monoclonal antibodies and antiviral drugs in Italian inborn errors of immunity patients during COVID-19 pandemic - Garzi, Giulia; Cinetto, Francesco; Firinu, Davide; Di Napoli, Giulia; Lagnese, Gianluca; Punziano, Alessandra; Bez, Patrick; Cinicola, Bianca Laura; Costanzo, Giulia; Scarpa, Riccardo; Pulvirenti, Federica; Rattazzi, Marcello; et al. (Frontiers in Immunology, 2022)
Background: Since the beginning of the COVID-19 pandemic, patients with Inborn Errors of Immunity have been infected by SARS-CoV-2 virus showing a spectrum of disease ranging from asymptomatic to severe COVID-19. A fair number of patients did not respond adequately to SARS-CoV-2 vaccinations, thus early therapeutic or prophylactic measures were needed to prevent severe or fatal course or COVID-19 and to reduce the burden of hospitalizations. Methods: Longitudinal, multicentric study on patients with Inborn Errors of Immunity immunized with mRNA vaccines treated with monoclonal antibodies and/or antiviral agents at the first infection and at reinfection by SARS-CoV-2. Analyses of efficacy were performed according to the different circulating SARS-CoV-2 strains. Results: The analysis of the cohort of 192 SARS-CoV-2 infected patients, across 26 months, showed the efficacy of antivirals on the risk of hospitalization, while mabs offered a positive effect on hospitalization, and COVID-19 severity. This protection was consistent across the alpha, delta and early omicron waves, although the emergence of BA.2 reduced the effect of available mabs. Hospitalized patients treated with mabs and antivirals had a lower risk of ICU admission. We reported 16 re-infections with a length of SARS-CoV-2 positivity at second infection shorter among patients treated with mabs. Treatments with antivirals and mabs were safe. Conclusions: The widespread use of specific therapy, vaccination and better access to care might have contributed to mitigate risk of mortality, hospital admission, and severe disease. However, the rapid spread of new viral strains underlines that mabs and antiviral beneficial effects should be re- evaluated over time.